Mechanical and metabolic responses during a high-intensity circuit training workout in competitive runners - Di Michele, R.; Del Curto, L.; Merni, F. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: This study aimed to assess the mechanical and metabolic responses of competitive runners throughout a high-intensity circuit training (HICT) workout, designed to improve explosive strength under acute metabolic fatigue. METHODS: Eight high-level endurance runners (age: 21.8±3.7 y; body mass: 61.5±5.7 kg; height: 175.2±5.2 cm; 1500-m record: 3 min 54±7s) completed an incremental exhaustive running test to determine the maximum oxygen uptake (VO2max) and maximum aerobic speed (MAS). The athletes then performed on a track a HICT workout, consisting of two identical circuits interspersed by 5-min of passive recovery. Each circuit was constituted by six 30-s dynamic or explosive strength exercises, alternated to 200-m runs (1000-m for the final run) at 90-95% of MAS. During a hopping exercise included in the circuit, and during the 1000-m run, lower limb stiffness measures were obtained from contact and flight times using a method based on the spring-mass model. RESULTS:Hopping stiffness was significantly lower (P0.05) in the first and the second circuit (8.08±1.49 vs. 7.87±1.31 kN/m), as well as vertical stiffness (33.56±5.25 vs. 32.16±5.45 kN/m). The mean VO2 in the 1000-m run of the two circuits was 93.17±3.56 % and 93.47±3.91 % of VO2max, respectively. CONCLUSION: Despite the occurrence of acute neuromuscular fatigue throughout the workout, the runners avoided an impairment of their stiffness during running. Furthermore, the relatively high percentage of VO2max achieved indicates the HICT involves also stimuli for aerobic conditioning.